Hospitalizations for cardiovascular diseases attributable to tobacco smoking in France in 2015. (13th November 2019) - Bonaldi, Christophe; Pasquereau, Anne; Hill, Catherine; Thomas, Daniel; Moutengou, Elodie; Thanh, Viêt Nguyen; Olié, Valérie
Abstract: Aims: Tobacco smoking is a major risk factor for many cardiovascular diseases. In France, the daily smoking prevalence is among the highest in high-income European countries. This study estimated the number of hospitalizations for cardiovascular diseases attributable to smoking in France in 2015, and the number of stays that could have been avoided if there had been 10% less current smokers or if the prevalence of current smokers had been 20%. Methods: Age- and sex-specific attributable fractions were calculated by combining relative risks extracted from the literature with the prevalence of smoking estimated in the 2014 Health Barometer, a national representative survey. These fractions were applied to hospitalization stays with a primary diagnosis for a cardiovascular disease whose risk is known to increase with smoking. Results: In France in 2015, 250, 813 hospital stays (95% uncertainty interval=234, 869–269, 807) related to a cardiovascular condition were estimated as attributable to smoking. This represented 21% of all stays for a cardiovascular condition. Ischemic heart disease accounted for the largest share of smoking-related stays (39%). If the number of current smokers had been 10% lower or if the prevalence of smoking in the population had dropped to below 20%, 5867 stays and 25, 911 stays, respectively, would have been prevented. Conclusions: In France, a large number of hospital stays for cardiovascular disease are attributable to tobacco smoking. A 10% reduction in smoking would avoid nearly 6000 hospital stays per year; more than 25, 000 annual hospital stays if only 20% of the French population smoked.